Description of four new species of the tiger moth genus Dysschema Hübner (Lepidoptera: Erebidae, Arctiinae, Arctiini, Pericopina) - Moraes, Simeão De Souza; Duarte, Marcelo (Zootaxa, 2015)
Description of four new species of the tiger moth genus Dysschema Hübner (Lepidoptera: Erebidae, Arctiinae, Arctiini, Pericopina). Four new species of Pericopina are described, three from southeast of Brazil: Dysschema uriasi Moraes, sp. nov., Dysschema wayneri Moraes, sp. nov., Dysschema amapoarum Moraes & Duarte sp. nov., and one from Mexico: Dysschema tarsoi Moraes sp. nov. Detailed species descriptions are based upon morphological characters. Photographs of habitus, illustrations of genitalia and comments on morphology are provided.